What About History ? - Brian Williams (Miles Kelly Publishing, 2004)
Questions and answers provide a beguiling and friendly way of accessing information for children. In this volume, answers come thick and fast in the top two-thirds of the spread with text and illustrations, while a panel in the lower third provides background information and images.
Keywords: Nonfiction -- Nonfiction